MEREKONSTRUKSI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SEKOLAH NEGERI STUDI KASUS SMA N 14 YOGYAKARTA - Siti Fatimah (EL-TARBAWI, 2018)
Great depression in 1930s and multidimensional crisis aftermath inspired some scholars to propose the idea of a new social order. Those scholars, the reconstructionist, see that it is necessary for human beings and humanity in order to survive the challenges to reconstruct their way of life: setting aside negative impacts of modernity while maintaining the good aspects. The reconstructionist see that education must play a role in building new social order by being involved in social movement and reconstruct the way of learning and teaching. In the context of learning PAI (islamic teachings educations) and morals in government schools, SMA N 4 Yogyakarta has adapted several methods relevant to the ideas of reconstructionism in education. SMA N 4 Yogyakarta has made use of cyber media as a way to develop students’ understanding about materials. This school also encouraged students to be involved in community development.Keywords: reconstructionism, islamic education, PAI.